Research status of east Asian traditional medicine treatment for chronic cough: A scoping review. - Boram Lee; Chan-Young Kwon; Ye Ji Kim; Jae Hyun Kim; Kwan-Il Kim; Beom-Joon Lee; Jun-Hwan Lee (PLoS ONE)
Background When patients continue to experience cough despite conventional treatment, East Asian traditional medicine (EATM) including herbal medicine and/or acupuncture has been frequently used. Previous systematic reviews of EATM treatment for chronic cough have been conducted mainly on herbal medicine, targeting patients with conditions that cause cough. In clinical practice, EATM interventions are not limited to herbal medicine, and considering that chronic cough is often caused by two or more conditions or unspecific causes, a comprehensive investigation is clinically relevant. We examined the current research status of EATM for chronic cough. Methods Based on Arksey and O'Malley's scoping review methodological framework, a total of six English, Chinese, Korean, and Japanese electronic databases were searched on August 2022. Any clinical studies on EATM targeting chronic cough patients (regardless of their cause) were included. Results Among 474 included studies, the study designs were mainly randomized controlled trials (72.4%), and the population was evenly distributed between children and adults. The cause of cough was not reported in most studies (56.1%). The common cause of cough was upper airway cough syndrome and post-respiratory infection (9.5%, each), followed by mixed cause (7.6%), nonspecific cause (5.9%), and gastroesophageal reflux disease (4.0%). EATM was conducted for a mean of 19.1 days, and herbal medicine was the most common (80.6%). Conventional medication was frequently used as a control (81.2%). For outcomes, the total effective rate was the most frequently utilized (94.3%), followed by cough severity (53.8%). EATM treatment showed positive outcomes in most studies. Conclusions In future EATM studies, it is necessary to either specify the cause of chronic cough or to report that the study was targeting nonspecific chronic cough. In addition, high-quality studies assessing the efficacy of EATM with placebo control treatment should be conducted, using validated evaluation tools.